The Impact of Ginger Compresses on Alleviating Rheumatic Discomfort Intensity in the Older Individuals at the Social Protection House - Erlinawati, N. Ai; Perceka, Andhika Lungguh; Rusyani, Herlin; Huda, Taufik; Awaludin, Aceng Ali (PT FORMOSA CENDEKIA GLOBAL, 2024)
Rheumatoid Arthritis is an illness that targets the joints, particularly in the limbs, which can cause pain. Pain management can use non-pharmacological management such as cutaneous stimulation, namely with warm ginger compresses. This non-pharmacological management can help relax the body so that it can block pain receptors that will be perceived in the brain. The general objective in the purpose of this study was to ascertain whether ginger compresses could lessen the intensity of elderly rheumatic discomfort at RPSTW Garut, West Java Province in 2023. Pre and posttest designs were used in a quasi-experimental research design..The study population was 75 people with sampling techniques using purposive sampling methods obtained a sample of 14 people. The results indicated that the average severity Assessing the severity of rheumatic pain prior to the application of ginger compress 6.07 with a deviation standard 0.730. While the typical level of pain after Posttest of was 2,79 with a standard deviation of 0.699. Based on the statistical analysis wilcoxon signed rank test obtained a significant impact analyzing the impact of ginger compresses on rheumatoid arthritis pain intensity among older individuals. Researchers suggest that it should be used as gerontic nursing knowledge material, especially complementary therapies and for it is advised to carry out additional studies again using a true experiment design so that the research results are better and the data obtained are more valid